Investigations of the mechanism of retention of electrochemically modulated liquid chromatography - Pimienta, Gloria Fe M. (ProQuest LLC, 2010)
Electrochemically modulated liquid chromatography is a technique which uses a column that is configured as a three-electrode electrochemical cell. The packing is a conductive material, serving both as a stationary phase and as a working electrode. Chromatographic retention is manipulated through changes in the potential applied to the stationary phase (Eapp) which alters interfacial properties such as surface charge and double layer structure. The stationary phase can thus be viewed as a compositionally tunable packing, with retention properties that can be adjusted to enhance separation efficiency. EMLC separations have been carried out to a wide variety of analyte mixtures, including aromatic sulfonates, monosubstituted benzenes and corticosteroids. EMLC can also be used as a tool for investigating electrosorption processes. The main goal of this dissertation is advance insights into the retention mechanism for EMLC. Previous works with charged analytes demonstrated the impact of ionic solute-stationary phase interactions in EMLC retention. The potential-dependent retention of neutral solutes implies a mechanism beyond electrostatics. Simple, neutral aromatic solutes are employed as test solutes to examine this fundamental issue. Benzene and a series of alkylbenzenes, and di- and tri- methylbenzenes are chosen in particular to probe EMLC-based retention with respect to solute structure and properties. Retention is monitored at porous graphitic carbon (PGC) stationary phase as a function of Eapp. The results are then interpreted based on the changes on the strength of solute-stationary phase interactions, including electron donor-acceptor, solvophobic interactions, and competitive adsorption from supporting electrolyte ions. In addition, various factors that influence EMLC retention of alkylbenzenes and methylbenzenes are investigated.